Canada's Rights Revolution: Social Movements and Social Change, 1937-1982 - Hayday, Matthew (Labour / Le Travail, 2009)
The article reviews the book, "Canada's Rights Revolution: Social Movements and Social Change, 1937-1982," by Dominique Clément.
Keywords: BOOKS – Reviews; CANADA – Politics & government – 20th century; CANADA'S Rights Revolution: Social Movements & Social Change 1937-1982 (Book); CLEMENT; Dominique; Nonfiction